ASPEK KOHESI DAN KOHERENSI DALAM PENULISAN KARANGAN DESKRIPSI YANG DISUSUN OLEH PEMBELAJAR BIPA (STUDI KASUS MAHASISWA THAMMASAT UNIVERSITY, BANGKOK PADA PROGRAM SEA-GATE UGM 2016) - Itaristanti Itaristanti (Indonesian Language Education and Literature, 2016)
The objective of this research is to present analysis toward several aspects in term of cohesion and coherence in writing paragraph of Indonesian language: in order to elaborate coherent paragraph for foreign learners or BIPA students. Other objective is to find the most suitable techniques for teaching essay writing for foreign learners. This research applies a qualitative method. The outcome of the research shows that the most common mistake is the use of conjunction.